1993
DOI: 10.1536/ihj.34.567
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Relation to Minnesota Code Items in Elderly Subjects. Sex-Related Differences in a Cardiovascular Study in the Elderly.

Abstract: The prognostic value of electrocardiographic abnormalities has not been widely studied in the elderly. We examined the Minnesota code ECG items in 2254 elderly subjects of the Cardiovascular Study in the Elderly (CASTEL), performed on an Italian general population. In our experience, codes for ischaemia, 1st-degree atrio-ventricular block, bundle branch blocks, myocardial infarction, atrial fibrillation or sinus tachycardia were predictors of overall mortality in females, while only the former three items were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…In most studies the analysis is purely descriptive and differences by sex, cardiovascular disease or functional capacity are not considered. Similarly, they do not discuss whether these findings are associated with a higher mortality in centenarians, as in a younger population [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In most studies the analysis is purely descriptive and differences by sex, cardiovascular disease or functional capacity are not considered. Similarly, they do not discuss whether these findings are associated with a higher mortality in centenarians, as in a younger population [24]. …”
Section: Discussionmentioning
confidence: 99%
“…This issue was dealt with in 2254 elderly subjects from the CAS-TEL. 27 A logistic regression showed a predictive role for overall mortality of ECG signs of ischaemia, bundle branch block (BBB) and atrio-ventricular block in males, and of ischaemia, myocardial infarction, BBB and atrial fibrillation in females. Taking into consideration cardiovascular mortality, atrial fibrillation, left BBB and ischaemia were predictors in both sexes, right BBB, LVH and supraventricular tachycardia were predictors in men, and A-V block in females.…”
Section: Other Ecg Abnormalitiesmentioning
confidence: 99%
“…In elderly subjects with atrial fibrillation, the RR of stroke is increased. 32) Finally, we have previously demonstrated 24) that in the Italian general population conduction defects independently increase mortality by 40 to 49%. The high prevalence of historical chronic diseases among the Cimbrians also deserves comment.…”
Section: Discussionmentioning
confidence: 92%
“…Register's Office reports indicate that they have greater cardiovascular mortality, 6) and the results reported here confirmed that they actually do have an inferior risk pattern compared to SCP of the same age class. In fact, practically all the most important risk factors (arterial hypertension, and namely systolic and pulse hypertension, 17,21) dislipidemia, 22) left ventricular hypertrophy, 23) atrial fibrillation, 24,25) and cardiac conduction defects 24) ) were more prevalent in the Leogra valley than in the SCP, and the prevalences of chronic diseases such as CAD, respiratory disease, intermittent claudication, and stroke were greater as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation